Individuality and the Moral Life (Analytic Teaching, 1988)
Introduction:  In their discussion on love and friendship, Millie tells Harry that what we love about someone or something are the qualities that makes them special.  As Harry phrases it, other people's differences are just what we like about them.  Two issues seem to be implied by these statements: first, what is special or unique about someone is an expression of individuality; second, those individual differences become precious to us as we enter into a significant relationship with another.